Numerical Analysis of Slotted Wings Using Fluid-Structure Interaction - Hassan, Makarim A.; Laftah, Rafil M.; Ismael, Muneer A. (Basrah Journal for Engineering Sciences, 2022)
For shorter landing and take-off path in airports, the aircrafts should reduce their speed with keeping high lifting force. This paper is to identify solutions to increase the lift force of the wing significantly under several flight scenarios (such as takeoff and landing) using leading-edge slats and their relationship with the dynamic parameters of the aerodynamic wing. The study is performed by the use of ABAQUS 2016 software. The problem is solved for turbulent flow and 2-dimensional composite wing at constant Reynolds’s number of (6.49 × 10 5 ) and constant boundary conditions. Various depths have been used for the auxiliary airfoil at constant width and gap. All stresses at the wing base were obtained. The pressure distribution on the airfoil surface was determined, air velocity distribution was tracked over the surface, lift and drag forces and their coefficients were computed. The results show that the highest value of the lift coefficient is 0.489 at the depth (-3 %) of the wing chord, it decreases when the depth of the slat becomes zero %, and the rise returns with increasing depth to (4 %), but it does not reach the maximum value, while the highest drag coefficient was (1.89) at depth (4 %) of the wing chord. The maximum value of Von Mises stress was found at depth of 4 % with value of 1.605 × 10 5 Pa.